Redox regulation of HIV-1: the thioredoxin pathway, oxidative metabolism, and latency control - Mangold, Jesse F.; Swartz, Talia H. (Frontiers in Physiology, 2025)
Redox homeostasis is a critical determinant of HIV-1 pathogenesis, influencing viral entry, transcription, latency, and persistence in distinct cellular reservoirs. The thioredoxin (Trx) system, a central antioxidant pathway, modulates the redox state of transcription factors and viral proteins while buffering oxidative stress. Paradoxically, while oxidative signals can drive HIV-1 gene expression, the virus also co-opts host antioxidant systems, such as thioredoxin (Trx) and glutathione (GSH), to support its replication and survival. In this review, we examine the multifaceted roles of the Trx pathway in HIV-1 infection, highlighting how redox regulation influences transcriptional activation through NF-κB and AP-1, and modulates the function of viral proteins, such as Tat. We further explore how oxidative metabolism intersects with redox balance to influence latency, particularly through cell-type-specific mechanisms in CD4+ T cells and myeloid cells. Emerging insights into thioredoxin-interacting protein (TXNIP) reveal a critical interface between glucose metabolism, ROS signaling, and latency control. Notably, interventions targeting redox homeostasis—whether antioxidant or pro-oxidant—exert divergent effects depending on the cellular reservoir, underscoring the need for tailored therapeutic strategies. By integrating redox biology and immunometabolism, we outline potential avenues to either stabilize latency or induce viral reactivation in pursuit of an HIV-1 cure.